Zadania logistyki międzynarodowej i eurologistyki w integracji i globalizacji gospodarki - Gołembska, Elżbieta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The contemporary role of international logistics, or broader - global logistics, is closely related to the first and second waves of economic globalization. A very important feature of globalization is the consistent lowering of transaction and communication costs brought about by technical advancements. The process of globalization can be characterized by identifying its major manifestations such as the world-wide network for trading goods and services, and the development of international transportation and information systems facilitating universal communication. The aim of the present paper is to identify and discuss the major tasks of international logistics in the process of economic globalization, with particular focus on eurologistics as an important case of international logistics. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 104-112